2023
DOI: 10.1038/s41440-022-01133-6
|View full text |Cite
|
Sign up to set email alerts
|

2022 Renal denervation therapy for the treatment of hypertension: a statement from the Thai Hypertension Society

Abstract: Hypertension remains a significant risk factor for major cardiovascular events worldwide. Poor adherence to treatment is extremely common in clinical practice, leading to uncontrolled hypertension. However, some patients with resistant hypertension still have uncontrolled blood pressure despite good medical compliance. A specific group of patients also develop adverse reactions to many blood pressure-lowering medications. These scenarios indicate that innovative strategies to lower blood pressure in challengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Then, risks may be pointed out that too many ablations may lead to increase complications. In other words, repeat ablation could cause perforation or stenosis, as described by Weranuj et al [2]. However, as far as I know, there is no such report.…”
Section: Multiple Ablationmentioning
confidence: 91%
See 2 more Smart Citations
“…Then, risks may be pointed out that too many ablations may lead to increase complications. In other words, repeat ablation could cause perforation or stenosis, as described by Weranuj et al [2]. However, as far as I know, there is no such report.…”
Section: Multiple Ablationmentioning
confidence: 91%
“…There is always a learning curve in the development of physicians' skills. This report presented by Weranuj et al [2]. emphasized that RDN should be performed by a welltrained and experienced operator who should understand the indications, contra-indications, and its procedure in detail.…”
Section: Learning Curvementioning
confidence: 99%
See 1 more Smart Citation
“…There is vast evidence of the importance of the SNS in the regulation of renal function and blood pressure (BP) [20,21] and its role in the progression of HF [20][21][22] and particularly in the development of the cardiorenal syndrome [2,[4][5][6]. RDN was originally introduced for the treatment of resistant hypertension and is now regarded a safe and effective procedure bringing long-term BP-lowering [23][24][25], therefore new clinical indications for its application beyond hypertension are considered [25][26][27]. Recent studies have suggested that RDN may be a promising tool in the treatment of HF and the cardiorenal syndrome [4,5,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, regardless of the ablation modality, confirming both the BP (BP)-lowering efficacy and safety of RDN in a broad range of patients with hypertension, including resistant hypertension [ 1 4 ]. Expert consensus in multiple countries and regions has proposed that RDN can be used as an adjunct treatment option for uncontrolled and resistant hypertension despite best efforts at lifestyle and pharmacologic interventions [ 5 , 6 ]. RDN may also be used in patients who are unable to tolerate antihypertensive medications in the long-term [ 7 ].…”
Section: Introductionmentioning
confidence: 99%